PENGARUH SUMBER DAYA MANUSIA, TEKNOLOGI INFORMASI DAN BUDAYA ORGANISASI TERHADAP IMPLEMENTASI STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL (Studi Empiris pada Satuan Kerja Daerah (SKPD) di Kota Pekanbaru) - Zuria Alhafziani; Yessi Mutia; Rofika Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The issuance of Government Regulation 71 Year 2010 concern the Government Accounting Standards (SAP) accrual-based and Regulation of the Minister of the Interior of the Republic Indonesia (Permendagri) 64 Year 2013 required the regional government included Pekanbaru to implement accrualbased financial statements started in 2015. The purpose of this study was to determine the influence of human resources, information technology and organizational culture on the implementation of government accounting standards accrual based in regional government. The object of this study is SKPD in Pekanbaru City. The data used is primary data obtained from distributed questionnaires to respondents were selected by purposive sampling technique. The reason and consideration that respondent in this study included employees who participate and determine the extent of accrual based accounting is applied in regional government. Data analysis methods used in this study is the multiple linear regression analysis by SPSS 17.0. The results of the road map study indicated that variable the human resources, information technology and organizational culture influence on the implementation of government accounting standards accrual based in regional government. Keywords : government accounting standards, accrual based, implementation, human resources, information technology, organizational culture, PP No.71 Tahun 2010, Permendagri No.64 Tahun 2013